1998
DOI: 10.1007/s11745-998-0234-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of n−3 fatty acid supplementation on lipid peroxidation and protein aggregation in rat erythrocyte membranes

Abstract: Human erythrocytes in the circulation undergo dynamic oxidative damage involving membrane lipid peroxidation and protein aggregation during aging. The present study was undertaken to determine the effect of n-3 fatty acid supplementation on lipid peroxidation and protein aggregation in the circulation and also the in vitro susceptibility of rat erythrocyte membranes to oxidative damage. Wistar male rats were fed a diet containing n-6 fatty acid-rich safflower oil or n-3 fatty acid-rich fish oil with an equal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 37 publications
2
20
0
Order By: Relevance
“…The higher susceptibility of n-3 PUFA-rich hepatocytes was consistent with that of the higher susceptibility of n-3 PUFA-rich dietary oil in an organic solvent. This is in agreement with the observation showing that erythrocyte membranes composed of high n-3 PUFA were less stable toward in vitro oxidation, 4) but not with the observation showing that free PUFA in micelle or liposome systems in an aqueous medium become more stable as the unsaturation increases. 31.32) With ADP/Fe(II) ion oxidation, while the degree of increased lipid peroxidation in the fish oil diet group was higher than that in the safflower oil diet group, the degree of DNA damage was similar.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The higher susceptibility of n-3 PUFA-rich hepatocytes was consistent with that of the higher susceptibility of n-3 PUFA-rich dietary oil in an organic solvent. This is in agreement with the observation showing that erythrocyte membranes composed of high n-3 PUFA were less stable toward in vitro oxidation, 4) but not with the observation showing that free PUFA in micelle or liposome systems in an aqueous medium become more stable as the unsaturation increases. 31.32) With ADP/Fe(II) ion oxidation, while the degree of increased lipid peroxidation in the fish oil diet group was higher than that in the safflower oil diet group, the degree of DNA damage was similar.…”
Section: Discussionsupporting
confidence: 90%
“…4) While the unsaturation index (UI), as expressed by the sum of percentages of individual fatty acidsϫthe number of double bonds, of fish oil (168) was equal to that of safflower oil (168), the peroxidizability index (PI), as expressed by the sum of percentages of individual fatty acidsϫnumber of active methylene groups, of fish oil (114) was higher than that of safflower oil (78). The peroxide and acid values of safflower oil were 1.1 neq/mg and 0.2, respectively, and those of fish oil were 1.2 neq/mg and 0.2, respectively.…”
mentioning
confidence: 99%
“…Excess intake of n-3 PUFA may reduce antioxidant status, 11,12,50,53,54 thus enhancing susceptibility to oxidative damage. Other investigators 13,14,55 could not find any change in antioxidant status in humans and rats treated with n-3 fatty acid-rich diet. On the contrary, Kesavulu et al 51 have demonstrated that the treatment of diabetic patients with n-3 fatty acids improved their antioxidant status.…”
Section: 2150-52mentioning
confidence: 88%
“…9,10 Contradictory results have been reported on n-3 PUFA consumption and lipid peroxidation, measured as thiobarbituric acid reactive substance (TBARS) levels. In fact, Wander et al 11 and Allard et al 12 have reported increased levels of TBARS in human plasma after consumption of n-3 fatty acids (EPA and DHA), whereas Nordoy et al 13 and Ando et al 14 could not find any significant differences in TBARS levels in their studies. However, several reports have shown the beneficial effects of fish oils containing n-3 polyunsaturated fatty acids (PUFAs) like eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) in the protection against lipid peroxidation in rat and human beings with diabetes.…”
Section: Introductionmentioning
confidence: 92%
“…For example, the obesity by the increase of TG concentration and the circulatory disease (Arteriosclerosis and Table 5 Effects of experimental diets on serum TG/PL, T-C/PL or T-C/HDL-C and LDL-C/HDL-C ratios in rats See footnote Table 1 2) a-f: Means with the same letter superscript in histograms are not significantly different at the 5% level by Duncan's multiple range test heart disease etc.) by increase of T-C and LDL-C can be given (Ando et al, 1998;Iwai et al, 2002). However, the rats fed on Cheonggukjang increased HDL-C and decreased for LDL-C, TG, and T-C.…”
Section: )mentioning
confidence: 99%